Chromogranin positive cells in colorectal carcinoma and transitional mucosa. - Mori, M (1995)
AIMS--Immunostaining of chromogranin identifies gastrointestinal mucosal endocrine cells. The detailed distribution and significance of chromogranin positive cells in colorectal carcinomas and in transitional mucosa remain unclear. The aim of this study was to clarify these aspects. METHODS--The distribution of chromogranin positive cells was studied by immunohistochemical methods in normal epithelium remote from carcinoma, in transitional mucosa, and in carcinomas of the colorectum. In selected cases northern or western blot analyses were performed. RESULTS--Chromogranin positive cells were seen in the lower third of the normal crypts and less frequently in transitional mucosa. Thirty five per cent (n = 38) of colorectal carcinomas showed immunohistochemically positive carcinoma cells in the tumour tissue. Northern and western blot analyses showed similar results. There was no difference in clinicopathological factors, including prognosis, between chromogranin positive cases of colorectal carcinoma (n = 38) and chromogranin negative cases (n = 70). CONCLUSIONS--Neuroendocrine cell differentiation is controlled in transitional mucosa and the presence of chromogranin positive cells in carcinoma tissue does not influence the patient's prognosis.